Follicular lymphoma regulatory T-cell origin and function - Rodriguez, Stéphane; Alizadeh, Mehdi; Lamaison, Claire; Saintamand, Alexis; Monvoisin, Céline; Jean, Rachel; Deleurme, Laurent; Martin-Subero, Jose Ignacio; Pangault, Céline; Cogné, Michel; Amé-Thomas, Patricia; Tarte, Karin (Frontiers in Immunology, 2024)
Introduction Follicular Lymphoma (FL) results from the malignant transformation of germinal center (GC) B cells. FL B cells display recurrent and diverse genetic alterations, some of them favoring their direct interaction with their cell microenvironment, including follicular helper T cells (Tfh). Although FL-Tfh key role is well-documented, the impact of their regulatory counterpart, the follicular regulatory T cell (Tfr) compartment, is still sparse. Methods The aim of this study was to characterize FL-Tfr phenotype by cytometry, gene expression profile, FL-Tfr origin by transcriptomic analysis, and functionality by in vitro assays. Results CD4+CXCR5+CD25hiICOS+ FL-Tfr displayed a regulatory program that is close to classical regulatory T cell (Treg) program, at the transcriptomic and methylome levels. Accordingly, Tfr imprinting stigmata were found on FL-Tfh and FL-B cells, compared to their physiological counterparts. In addition, FL-Tfr co-culture with autologous FL-Tfh or cytotoxic FL-CD8+ T cells inhibited their proliferation in vitro. Finally, although FL-Tfr shared many characteristics with Treg, TCR sequencing analyses demonstrated that part of them derived from precursors shared with FL-Tfh. Discussion Altogether, these findings uncover the role and origin of a Tfr subset in FL niche and may be useful for lymphomagenesis knowledge and therapeutic management.